Reproductive sink enhanced drought induced senescence in wheat fertile line is associated with loss of antioxidant competence compared to its CMS line - Semwal, Vimal Kumar (Physiol Mol Biol Plants, 2018)
Reproductive sinks regulate monocarpic senescence in wheat as desinking delayed flag leaf senescence under irrigated condition. In this study, wheat cv. HW 2041 and its isonuclear male sterile line (CMS) were subjected to post-anthesis water deficit stress to understand the association between sink strength, senescence and drought response in relation to oxidative stress and antioxidant defense at cellular and sub-cellular level. CMS plants maintained better water relations and exhibited delayed onset and progression of flag leaf senescence in terms of green leaf area, chlorophyll and protein content than fertile plants under water deficit stress (WDS). Delayed senescence in CMS plants under water deficit stress was associated with less reactive oxygen species generation, lower damage to membranes and better antioxidant defense both in terms of antioxidant enzyme activities and metabolite content compared to fertile plants. Expression of some senescence associated genes (SAGs) such as WRKY transcription factor (WRKY53), glutamine synthetase1 (GS1), wheat cysteine protease (WCP2) and wheat serine protease (WSP) was lower while catalse 2 (CAT2) transcript levels were higher in the CMS plants compared to HW2041 during senescence under water deficit stress. Antioxidant defense in chloroplasts was better in CMS line under water deficit stress compared to HW2041. This is the first report showing that reproductive sink enhanced drought induced senescence in flag leaf of wheat fertile line is associated with higher oxidative stress and damage and loss of antioxidant competence compared to its sterile line under water deficit stress. Higher expression of some SAGs and decline in superoxide dismutase and ascorbate peroxidase activity in the chloroplasts also contributed to the accelerated senescence in fertile line compared to its CMS line under WDS. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12298-018-0549-9) contains supplementary material, which is available to authorized users.